Defective Pulmonary Innate Immune Responses Post-Stem Cell Transplantation; Review and Results from One Model System - Domingo-Gonzalez, Racquel; Moore, Bethany B. (Frontiers in Immunology, 2013)
Infectious pulmonary complications limit the success of hematopoietic stem cell transplantation (HSCT) as a therapy for malignant and nonmalignant disorders. Susceptibility to pathogens in both autologous and allogeneic HSCT recipients persists despite successful immune reconstitution. As studying the causal effects of these immune defects in the human population can be limiting, a bone marrow transplant (BMT) mouse model can be used to understand the defect in mounting a productive innate immune response post-transplantation. When syngeneic BMT is performed, this system allows the study of BMT-induced alterations in innate immune cell function that are independent of the confounding effects of immunosuppressive therapy and graft-versus-host disease. Studies from several laboratories, including our own show that pulmonary susceptibility to bacterial infections post-BMT are largely due to alterations in the lung alveolar macrophages. Changes in these cells post-BMT include cytokine and eicosanoid dysregulations, scavenger receptor alterations, changes in micro RNA profiles, and alterations in intracellular signaling molecules that limit bacterial phagocytosis and killing. The changes that occur highlight mechanisms that promote susceptibility to infections commonly afflicting HSCT recipients and provide insight into therapeutic targets that may improve patient outcomes post-HSCT.